Extinction debts and colonization credits of non-forest plants in the European Alps - Sabine B. Rumpf (Nature Portfolio, 2019)
Mismatches between the pace of climate change and plant responses may lead to delayed upslope shifts or extinction of mountain species. Here the authors investigate 135 alpine plant species, finding that extinction debts are more common among cold-adapted plants and colonization credits among warm-adapted plants.